The law-enforcement system in the civil rights and freedoms protection system: the international comparative aspect - O. Loskutov, Tymur (2020)
The article focuses on the problem of place determination of law-enforcement agencies in the civil rights and freedoms protection system. The emphasis is given to the analysis of international legal instruments in this sphere, in particular: the Convention for the Protection of Human Rights and Fundamental Freedoms; the International Covenant on Civil and Political Rights; the International Covenant on Economic, Social and Cultural Rights; the EU Charter of Fundamental Rights. The article has proved that law enforcement agencies are mainly aimed at ensuring and protection of human and citizen civil rights and freedoms in all spheres of social relations.